FAKTOR-FAKTOR YANG MEMPEGARUHI FIRM VAUE PADA PERUSAHAAN NON KEUANGAN DI BURSA EFEK INDONESIA - Marleen Aurellia; Apit Susanti (Pusat Penelitian dan Pengabdian kepada Masyarakat Sekolah Tinggi Ilmu Ekonomi Trisakti, 2022)
The purpose of this research is to examine the factors that can influence firm value in non-financial companies. This research uses eight independent variables: Dividend Policy, Institutional Ownership, Funding Policy, Profitability, Firm Size, Activity Ratio, Firm Growth, Liquidity and Firm Value as the dependent variable. The sampling method used is purposive sampling. This research uses 49 samples of non-financial companies listed on the Indonesia Stock Exchange (IDX) from 2018 to 2020, thus there are 147 data as samples. This research uses multiple linear regression for hypothesis testing. The result of this research exposed that Profitability, Firm size, and Liquidity have impact on firm value. If the probability of the company is high, it proves that the company is able to manage the company and generate high profits. If the company is able to pay its short-term obligations when they fall due, then the value of the company will be higher. Because the larger the size of the company or the scale of the company, the easier it will be for companies to obtain internal and external sources of funding. However Institutional ownership, Dividend policy, Funding policy, Firm growth and activity ratio have no impact on firm value.